1960
DOI: 10.2170/jjphysiol.10.267
|View full text |Cite
|
Sign up to set email alerts
|

NARCOTIC AND NaCl-DEFICIENCY AS BLOCKING AGENTS

Abstract: The conduction block of nerve is resulted generally from threshold elevation or action potential reduction, or by both combined in abnormal conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1962
1962
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…A preliminary report of some of the results has been made to the Physiological Society (Nathan & Sears, 1960b); since that time, similar findings by Uehara (1958Uehara ( , 1960 have come to our notice. Working on 376 P. W. NATHAN AND T. A. SEARS single myelinated fibres of the frog, she has also found that fibres of different sizes are blocked by different critical concentrations both of sodium ions and of local anaesthetics.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…A preliminary report of some of the results has been made to the Physiological Society (Nathan & Sears, 1960b); since that time, similar findings by Uehara (1958Uehara ( , 1960 have come to our notice. Working on 376 P. W. NATHAN AND T. A. SEARS single myelinated fibres of the frog, she has also found that fibres of different sizes are blocked by different critical concentrations both of sodium ions and of local anaesthetics.…”
supporting
confidence: 59%
“…It is evident that if small fibres have a lower safety factor than these large fibres, a lesser reduction in the nodal action current will cause conduction to fail in them. We have been unable to find any published figures for the safety factor of small fibres.A preliminary report of some of the results has been made to the Physiological Society (Nathan & Sears, 1960b); since that time, similar findings by Uehara (1958Uehara ( , 1960 …”
mentioning
confidence: 65%
“…I pm), the synaptic boutons (en passage sypapses) and the absence of the myelin sheath distinguish the internal hippocampal axons from the fimbria axon5 (Andersen 1960, Westrum & Blackstad 1962. T h e inverse relationship between fibre diameter and blocking concentration (Gasser & Erlanger 1929, Nathan 8z Sears 1961, Uehara 1960, Staiman & Seeman 1974) applies primarily, however, to fibres of the same type (Nathan & Sears 1961) and does not necessarily explain the difference observed in the present study. T h e bouton region of the unmyelinated fibres need to be considered both due to the presence of calcium channels and due to that the large increase in axon diameter map make this a low safety factor region (Jack et al 1983).…”
Section: Discussionmentioning
confidence: 53%
“…These studies were performed on myelinated fibres, several times thicker than the thin, unmyelinated fibres of the brain. As for local anaesthetics (Gasser & Erlanger 1929, Nathan & Sears 1961, the effect of volatile anaesthetics may be inversely related to fibre diameter (Uehara 1960). In addition, the absence of the myelin sheath calls for a closer look at the effect on these fibres, particularly as the susceptibility of synaptic transmission to anaesthetic agents has been suggested to reflect a low safety factor for impulse conduction in very In the present paper we compare the effect of the comparatively new, volatile anaesthetic isoflurane on two different parts of the same input system to the hippocampal CAI region.…”
mentioning
confidence: 99%